Fragile African States: What Should Donors Do? - Paul Collier (Fondation pour les études et recherches sur le développement international (FERDI), 2014)
1. IntroductionNecessarily, all donors will focus increasingly on fragile states. The more successful countries in Africa have achieved growing tax bases and are consequently now gaining access to global capital markets. For such countries, aid is becoming marginal. In contrast, fragile states, by the nature of their condition, have small tax bases and face risks which deter private capital: for them aid remains potentially important. Not only do donors provide a substantial proportion of government revenues; they bring expertise which is sorely lacking in fragile states; and they change incentives for government both intentionally through the conditions they set, and unintentionally through the revenues and expertise they provide.Donor practices have evolved considerably over recent decades. Donors have gradually learned how to operate effectively in those states which have governments that are reasonably representative of the interests of their citizens, and reasonably competent in managing public spending. In such states budget support free of policy conditions is likely to be the most effective modality for providing aid. Government ownership of an aid program maximizes the benefit from the superior local knowledge that it has, and minimizes interference in the accountability of government to citizens. Unfortunately, fragile states are not usually characterized by the combination of governments that are reasonably representative of the interests of their citizens, and reasonably competent in managing public spending: if they had both of these characteristics they would probably not be fragile. Yet without these characteristics, unconditional budget support is liable to be ineffective and can easily be counterproductive. Donor money is unlikely to be well-spent and can undermine the capacities that the state needs to develop. Donors therefore appear to face a dilemma. If the neediest countries are those in which aid is least effective, in allocating aid between countries the donor is faced with an uncomfortable trade-off between need and effectiveness.
Keywords: 330